Clinical characteristics and biomarkers feature analysis using a proteomics platform in young patients with acute coronary syndrome - Zhang, Kandi; Wang, Fengdan; Yu, Quan; Song, Yanqiong; Gu, Jun; He, Qing; Zhang, Junfeng (Frontiers in Cardiovascular Medicine, 2024)
Background: Acute coronary syndrome (ACS) is a leading cause of morbidity and mortality worldwide. In recent years, ACS has been reported to be associated with age, and the incidence has become more common in younger patients. Previous studies have identified various risk factors that contribute to the stratification of ACS patients.However, it remains unclear whether these risk factors, along with proteomic and clinical characteristics, are applicable to young ACS patients, as they are for middleaged and elderly patients. This study aimed to investigate the proteomics, risk factors, and clinical characteristics of young ACS patients, as well as the differences between them and middle-aged and elderly ACS patients.Methods: This observational study included a total of 187 participants diagnosed with ACS and 17 young healthy individuals as the control group. ACS patients were divided into three age groups: <45 years old, 45-60 years old, and 61-75 years old. The control group consisted of healthy individuals under the age of 45 who underwent coronary angiography and were excluded from CAD. We collected clinical characteristics, laboratory data, and echocardiographic results from each participant. Additionally, blood samples were collected for further analysis of relevant proteomic and arteriosclerosis marker data using proteomics analysis.Results: Our findings revealed that the presence of certain key factors was associated with a significantly difference in patients with ACS aged younger than 45 years, and this association differed from that of traditional cardiovascular risk factors in patients older than 45 years. Specifically, a higher body mass index and hyperlipidemia were found to be associated with an increased risk of ACS morbidity in young adults (<45 years old) compared to middle-aged and elderly individuals. Furthermore, our findings indicated that the expression levels of growth differentiation factor 15, osteopontin, and NT-proBNP were significantly different among the groups.In summary, our study revealed that the main pathogenic factors of ACS patients under 45 years of age differed from those of middle-aged and elderly patients.These findings may contribute to the prevention and treatment strategies for young patients with ACS.